How Much Food Loss and Waste Do Countries with Problems with Food Security Generate? - Daniel Durán-Sandoval; Gemma Durán-Romero; Francesca Uleri (Agriculture, 2023)
Worldwide, the number of people suffering from hunger is around 702 and 828 million, and 2.3 billion people have moderate or severe food insecurity. This situation is striking, considering that the vast amount of food discarded globally equals 1.3 billion tons annually. For this reason, in 2015, world leaders agreed to a global agenda for 2030, adopting the Sustainable Development Goals (SDGs). Among its objectives, are to fight against poverty, hunger, and gender inequality worldwide and achieve environmental sustainability. With this framework, this article uses a top-down mass balance approach to calculate food loss and waste (FLW) by country’s food security level. In addition, it explores the causes of FLW and its impacts on natural resources, climate change, food security, and the SDGs in countries with a weak and moderate level of food security. The estimated global FLW was 1498 million tons of food in 2017. The most food discarded was concentrated in countries with good food security, 894.3 million tons. In contrast, the lowest food discard occurred in countries with a weak level of food security, 11.4 million tons. The primary outcome of this paper is to establish a link between the levels of food security and food loss in different countries, which may serve as a guide for the design of specific public policies.